Histological structure of the Eye in Tree Frog Hyla arborea savignyi - Roaa S. Al-rawi; Nahla A. Al-Bakri (Journal of Madenat Alelem University College, 2011)
This research was conducted to study the histological structure of the eye in the tree frog (Hyla arborea savignyi) and showed that it is composed of the eyeball and the lens and optic nerve. Appeared eyeball is surrounded by three Tunica from the inside to the outside are Tunica Interna, Tunica vasculosa, Tunica fibrosa. The tunica interna consists of the retina that consists of 10 layers are from outer to inner pigment epithelial layer, rods and cones layer, external limiting membrane, outer nuclear layer, outer plexiform layer, inner nuclear layer, inner plexiform layer , ganglion cells layer , nerve fibers layer, internal limiting membrane .The vascular tunic or Uvea consists of the choroid, ciliary body , and iris . The fibrous coat consists of sclera ,cornea ,limbus cornea. The lens showed Biconvex discoid.